2016
DOI: 10.1155/2016/8984704
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Teaching Anatomy: Do Prosected Cross Sections Improve Students Understanding of Spatial and Radiological Anatomy?

Abstract: Introduction. Cadaveric dissections and prosections have traditionally been part of undergraduate medical teaching. Materials and Methods. Hundred and fifty-nine first-year students in the Faculty of Medicine, University of Colombo, were invited to participate in the above study. Students were randomly allocated to two age and gender matched groups. Both groups were exposed to identical series of lectures regarding anatomy of the abdomen and conventional cadaveric prosections of the abdomen. The test group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Another meta-analysis concluded that students can train spatial ability using cross-sections and mental rotation exercises (Langlois et al, 2017). Other studies reaffirmed that cross-sectional anatomy contributed significantly to visualizing anatomical structures in three dimensions (Lord, 1985;Provo et al, 2002;Samarakoon et al, 2016) underlining that studying neuroanatomy using cross-sections significantly improves cross-sectional anatomy knowledge.…”
Section: Students' Opinions About the Effects Of Greymapp-augmented Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Another meta-analysis concluded that students can train spatial ability using cross-sections and mental rotation exercises (Langlois et al, 2017). Other studies reaffirmed that cross-sectional anatomy contributed significantly to visualizing anatomical structures in three dimensions (Lord, 1985;Provo et al, 2002;Samarakoon et al, 2016) underlining that studying neuroanatomy using cross-sections significantly improves cross-sectional anatomy knowledge.…”
Section: Students' Opinions About the Effects Of Greymapp-augmented Rmentioning
confidence: 99%
“…Teaching and studying cross-sectional anatomy, although demanding, remains of crucial importance for students. Current doctors routinely encounter cross-sectional anatomy, and with the rapid development of modern medical imaging technologies, the number of future doctors who will be working with cross-sectional anatomy will increase as well (Samarakoon et al, 2016). It remains of crucial importance, therefore, for (bio)medical students to study cross-sectional anatomy.…”
Section: Students' Opinions About the Effects Of Greymapp-augmented Rmentioning
confidence: 99%
“…Traditional methods can be transformed to enhance anatomical learning, as demonstrated in the study. 7 This is important for educators to acknowledge when considering the best strategy for teaching anatomy. More efficient anatomical learning can be achieved by modifying existing methods; not necessarily requiring advanced technology.…”
Section: Cadaveric Materialsmentioning
confidence: 99%
“…Kerby et al4 found that dissection was overall most “fit for purpose” in meeting learning outcomes among Nottingham University Students and Imperial College London, but no single teaching modality met all aspects of the curriculum. Bowman et al2 in Australia among students of Central Queensland (CQ) University found ultrasound scan as the most preferred method of delivering anatomical information and dissection was the least favored teaching method, Swarmy and Searle1 found that ultrasound scan with cross-sectional images and line diagrams should be used as adjunct to teaching anatomy for medical students in New Zealand, Samarakoon et al14 in Sri Lanka among medical students of University of Colombo also found that cadaveric cross-sectional prosections may help students to understand spatial and radiological anatomy.…”
Section: Discussionmentioning
confidence: 99%